Tribal Land Conflicts and State Forestry in Odisha: A Historical Study - Rout, Naresh (International Journal of Social Sciences and Management, 2015)
The history of human existence and civilizations are intertwined with forests and trees. Forests are crucial for the goods and services they provide, which people all over the world depend on. Strategies to enhance the contributions of the world’s forests to social development, livelihoods and poverty eradication are vital at a time when unsustainable practices and economic crises continue to threaten healthy forests and the people who depend upon them. The survival of tribal communities critically depends on land and forest resources. For historical and ecological reasons, most tribal people inhabit the forest and highly inaccessible regions of the state. These communities practise various customary land tenure systems, which have often been modified by state policies and legislation. The clan-based land tenure system was based on customary rights over land, trees and forest. The land use and tenure systems vary from tribe to tribe, as reflected in the practice and terraced cultivation. The relationship between tribal people and forest resources has been symbiotic in nature. The life-way processes of Odisha’s tribal people are reflected in their economy, religion, polity and social institutions, which cannot be understood without understanding various aspects of the forest surrounding them. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12423 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 143-147